The synthesis of fructooligosaccharides by the fructofuranosidase FopAp from Aspergillus niger - Pindura, Mitchell Kingsley Chido (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2012)
Fructooligosaccharides (FOS) are short-chain fructans with a terminal glucose moiety and are found naturally in many plant species. Besides their wide use as an alternative sweetener in food and beverage industry, FOS have shown great potential as neutraceuticals against diabetes, colon cancer and bowel disease. The uses of FOS are dependent on the degree of polymerisation that they exhibit. Î²-fructofuranosidase (FFase) and fructosyltransferase (FTase) enzymes are capable of synthesing FOS from carbohydrate raw materials such as chicory and sugar beet. The aim of this study was to investigate the synthesis of FOS of a pre-defined chain length, from sucrose, by the enzyme FopAp; a Î²-fructofuranosidase from Aspergillus niger. ATCC 20611. The crude enzyme FopAp was successfully purified, with a yield of 78.20 %, by ammonium sulphate precipitation and anion exchange chromatography. Two protein fractions, named FA and FB were shown to exhibit FFase activity. SDS PAGE analysis revealed two proteins with molecular weights of 112 kDa and 78 kDa, which were identified as a FFase and a hydrolase. Temperature and pH optima of 20 ÂºC and 9, respectively, were observed for the transfructosylation activity in the FFase. The purified FFase exhibited a half life of 1.5 hrs under optimal conditions. Substrate kinetic studies indicated a high hydrolytic activity at low sucrose concentrations, with Vmax and Km of 1.25 Î¼mol/ml/min and 3.28 mM, respectively. Analysis by response surface methodology identified temperature and pH to be significant factors for the production of kestose and nystose, at a 95 % level of confidence. These findings were confirmed by neural networks constructed to identify optimal conditions of FOS synthesis.FOS synthesis was found to be optimal between pH 6 and pH 9 at 25 ÂºC. The factor of reaction time was found to be insignificant within the selected experimental constraints, for both FOS species. The findings of this investigation are very important as the foundations of a commercially viable synthetic process for the production of FOS.
Keywords: Aspergillus niger; Oligosaccharides